ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN DAN MEMPERTAHANKAN JUMLAH TAMU (SURVEI PADA TAMU HOTEL DI TASIKMALAYA) - R. Soni Sumali; Tuti Iriani; Mila Karmila (Bajang Institute, 2024)
The purpose of this study is to identify and analyze the marketing strategies implemented in an effort to increase and maintain the number of guests visiting hotels in Tasikmalaya. The method used in this research is descriptive method with 80 guests from 10 (ten) hotels in Tasikmalaya as respondents. Based on the results of the analysis test, it was found that the value of the marketing strategy had a significant influence on the number of guests at the Tasikmalaya Hotel